2001
DOI: 10.1111/j.1744-618x.2001.tb00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Religiousness: Differentiating the Diagnoses Through a Review of the Nursing Literature

Abstract: PURPOSE. To differentiate the definitions of spirituality and religiousness as used in nursing literature. DATA SOURCES. Journal articles, books, book chapters. DATA SYNTHESIS. The nursing literature has been inconsistent in defining spirituality and religiousness. The spirituality literature defines spirituality as the broader concept, with religiousness as a subconcept, while the religiousness literature defines religiousness as the broader concept, with spirituality as a subconcept. CONCLUSIONS. Spiritua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 10 publications
0
53
0
8
Order By: Relevance
“…A literature review by Dyson, Cobb, and Forman (1997) revealed several themes common to different conceptualizations of spirituality: a search for meaning in life, the need for hope, relatedness or connectedness to others, a set of religious or non-religious beliefs, and expression of spirituality in multiple ways. Other researchers who are writing on the construct of spirituality seem to refer to spirituality as having to do with four different phenomena: (1) an internal belief system (c.f., Burkhart & Solari-Twadell, 2001;Cook et al, 2000;Emmons & Crumpler, 1999;Hawks, 1994), (2) the construction of meaning (c.f., Benjamin & Looby, 1998;Burke & Hackney, 1999;Burkhart & Solari-Twadell, 2001;Erickson, Hecker, Kirkpatrick, Killmer, & James, 2002;Shafranske & Gorsuch, 1984), (3) a relationship (c.f., Burke & Hackney, 1999;Burkhart & Solari-Twadell, 2001;Dyson et al, 1997), and (4) a higher power or an ultimate reality (c.f., Benjamin & Looby, 1998;Burke & Hackney, 1999;Sigmund, 2002;Wolf & Stevens, 2001). Along with religiousness and spirituality, the term faith sometimes also appears in the literature to describe similar phenomena.…”
Section: Weaknesses In Previous Clinical Judgment Faith Bias Studiesmentioning
confidence: 99%
“…A literature review by Dyson, Cobb, and Forman (1997) revealed several themes common to different conceptualizations of spirituality: a search for meaning in life, the need for hope, relatedness or connectedness to others, a set of religious or non-religious beliefs, and expression of spirituality in multiple ways. Other researchers who are writing on the construct of spirituality seem to refer to spirituality as having to do with four different phenomena: (1) an internal belief system (c.f., Burkhart & Solari-Twadell, 2001;Cook et al, 2000;Emmons & Crumpler, 1999;Hawks, 1994), (2) the construction of meaning (c.f., Benjamin & Looby, 1998;Burke & Hackney, 1999;Burkhart & Solari-Twadell, 2001;Erickson, Hecker, Kirkpatrick, Killmer, & James, 2002;Shafranske & Gorsuch, 1984), (3) a relationship (c.f., Burke & Hackney, 1999;Burkhart & Solari-Twadell, 2001;Dyson et al, 1997), and (4) a higher power or an ultimate reality (c.f., Benjamin & Looby, 1998;Burke & Hackney, 1999;Sigmund, 2002;Wolf & Stevens, 2001). Along with religiousness and spirituality, the term faith sometimes also appears in the literature to describe similar phenomena.…”
Section: Weaknesses In Previous Clinical Judgment Faith Bias Studiesmentioning
confidence: 99%
“…Diversos estudios han demostrado una implicación importante de la dimensión espiritual a la hora de hacer frente a la enfermedad crónica y terminal, y se han encontrado correlaciones positivas entre los índices de recuperación y la espiritualidad (2,3,4). Estas investigaciones demuestran que, en un alto porcentaje, los individuos creen en un ser superior, y creen en el poder de este para mejorar el curso de la enfermedad (5,6,7,8,9).…”
Section: Introductionunclassified
“…The literature associates spirituality with interconnectedness (Kinjerski and Skrypnek 2004;Joseph 2002) and faith relationships with the transcendent (Beazley 1998). Interfaith studies of spirituality in diverse cultures and in different fields such as health care (Burkhart 2001), neurotheology (Newberg et al 2001), theology (Rose 2001) and psychology (Piedmont 2007) also find connection a central idea in the conceptualisation of spirituality.…”
Section: Similarities Between Workplace Spirituality and Maslow's Workmentioning
confidence: 99%